(untitled) (Revista Nacional de Administración, 2014)
El siguiente artículo analiza el ingreso de capital financiero de corto plazo (capital golondrina) en el país a partir del segundo semestre de 2012. Interesa revisar lo que establece la teoría económica sobre su origen, causas y consecuencias, así como las medidas regulatorias que pueden tomar las autoridades económicas para limitar estos flujos y contrarrestar sus efectos macroeconómicos. Finalmente, a la luz de estos desarrollos se revisa la propuesta del Poder Ejecutivo tendente a desestimular el arribo de estos capitales. ABSTRACT In this paper we analyze the entry of short-term financial capitals to the country in the second half of 2012. What economic theory says regarding its origin, causes and consequences is going to be reviewed, as well as the regulatory measures that policymakers can take to limit their flows and counteract their macroeconomic effects. Finally, taking into account these developments, an executive proposal aiming to discourage the arrival of these capitals is analyzed. KEYWORDS: CAPITAL FLOWS, IMPOSSIBLE TRINITY, INTEREST RATES, EXCHANGE RATES, INFLATION, INTERNATIONAL MONETARY RESERVES.